PEMBELAJARAN PENGOPERASIAN PINTU PERLINTASAN SEBIDANG KERETA API (Politeknik Perkeretaapian Indonesia Madiun, 2022)
The purpose of implementing this community service program is to increase expertise in operating crossing gates on barred and guarded railroads (service crossings). In this learning refresher activity, the demonstration method is carried out, which provides opportunities for learning participants to relate directly to the material being studied and demonstrate it. To find out the participants' understanding of the implementation of the trial, they immediately opened and closed the level crossing gates. The results from the implementation of refresh learning which are considered very effective can provide direct understanding and refresher regarding the correct operational standards of crossing gates.